Customer relationship management (CRM) in healthcare organization: A review of ten years of research - Baashar, Y.M. (Institute of Electrical and Electronics Engineers Inc., 2016)
the main objective of this paper is to review the existing studies regarding customer relationship management (CRM) in healthcare organization between 2005 and 2015. MEDLINE, Web of science, Scopus, ACM Digital Library, Emerald Management, ScienceDirect, IEEExplore, SpringerLink, and Google scholar were comprehensively searched using the terms 'customer relationship management', Or 'CRM', AND 'healthcare'. Forty-one articles were found, selected and carefully reviewed to their direct relevance and significance. Findings indicate that there is a lack of CRM research in the field of healthcare as in general, and the concept of CRM is new to the healthcare field as the amount of studies has grown significantly from 2010. Furthermore, the existing research regarding CRM in healthcare falls into four main classifications - (1) CRM in general, (2) e-CRM, (3) implementation, and (4) adoption. Issues and subjects regarding each CRM research classification was discussed. However, most of the found studies were conducted based on a review method, in which more empirical evidence is needed. Â© 2016 IEEE.